ANALISIS PENGARUH PENGANGGURAN, FOREIGN DIRECT INVESMENT (FDI) DAN MANUFAKTUR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (PERIODE TAHUN 2016-2021) - Wira Ganet Aribowo (JAMER : Jurnal Akuntansi Merdeka, 2023)
Several economic theories can explain economic growth, but what is popular to explain the relevance of the relationship between economic growth, Foreign Direct Investment, Manufacturing and Unemployment is the neoclassical theory where capital flows "downhill" from rich countries (capital abundance) to poor countries (capital scarce). So that all countries can access the same technology and produce similar goods, while the difference in per capita income reflects the difference in the rate of return on capital, new investment will be made in poor countries. On the other hand, the Heckscher-Ohlin model explicitly predicts capital flowing from countries with low interest rates to countries with high interest rates (Pogoda, 2012). After the 1997-1998 economic crisis, in 1999 Indonesia became a member of the G-20 making it a middle income country. More than two decades, Indonesia is in the middle income trap. Within the limits of this study, data were taken for 2016 – 2021, where foreign direct investment, manufacturing and unemployment had an effect on economic growth in Indonesia. As quoted in the World Bank report, Indonesia's per capita income was recorded at US$3,870 in the 2020 World Bank report, making it a lower middle income country. However, in 2021, in a World Bank report, Indonesia's per capita income recorded US$4,140, returning to the upper middle income country class.